Hypothalamic Neurochemical Changes in Long-Term Recovered Bilateral Subdiaphragmatic Vagotomized Rats - Kobrzycka, Anna Teresa; Stankiewicz, Adrian Mateusz; Goscik, Joanna; Gora, Monika; Burzynska, Beata; Iwanicka-Nowicka, Roksana; Pierzchala-Koziec, Krystyna; Wieczorek, Marek (Frontiers in Behavioral Neuroscience, 2022)
Background: Vagus nerve is one of the crucial routes in communication between the immune and central nervous systems. The impaired vagal nerve function may intensify peripheral inflammatory processes. This effect subsides along with prolonged recovery after permanent nerve injury. One of the results of such compensation is a normalized plasma concentration of stress hormone corticosterone – a marker of hypothalamic-pituitary-adrenal (HPA) axis activity. In the present work, we strive to explain this corticosterone normalization by studying the mechanisms responsible for compensation-related neurochemical alterations in the hypothalamus. Methods: Using microarrays and HPLC we measured genome-wide gene expression and major amino acid neurotransmitters content in the hypothalamus of bilaterally vagotomized rats, one month after surgery. Results: Our results show that, in the long-term, vagotomy affects hypothalamic amino acids concentration but not mRNA expression of tested genes. Discussion: We propose an alternative pathway of immune to CNS communication after vagotomy, leading to activation of the HPA axis, by influencing central amino acids and subsequent monoaminergic neurotransmission.